Pesquisa de Toxoplasma gondii (Nicolle & Manceaux, 1909) em sêmen, testículos e epidídimos de gatos (Felis catus) primoinfectados - Teixeira, Weslen Fabricio Pires [UNESP] (2014)
This study aimed to investigate the presence of T. gondii in semen, testicles and epididymis of cats experimentally infected with this coccidia. Therefore, twelve mongrel male cats of reproductive age and serologically negative for T. gondii were selected and divided into three experimental groups, GI: inoculated with 600 tissue cysts of T. gondii (P strain), GII : inoculated 2x105 tachyzoites (strain HR), and GIII: not inoculated (control group). Prior to inoculation (days -7 and 0) and days 7º, 14º, 21º, 28º, 42º, 56º and 70º post-inoculation (PID), all cats underwent clinical, serological (IFA) and haematological (blood count and parasitemia by T. gondii) examinations. Semen samples were obtained (eletroejaculation) those dates, and later held the T. gondii search by nested PCR and bioassay in mice. On 70º PID, the twelve cats were castrated, and their testicles and epididymis were evaluated for the presence of the parasite (PCR, bioassay in mice, and histopathological and immunohistochemical analyzes). All cats inoculated with T. gondii (GI and GII), seroconverted to T. gondii infection and showed parasitemia peaks in different experimental days post inoculation. The cats inoculated with the RH strain (GII) had higher titers than those inoculated with the P strain (GI). In these animals (GII) were also diagnosed more parasitemia and clinical changes compared to those belonging to Group I. In no trial date was diagnosed (bioassay and nested PCR) the presence of T. gondii in semen samples taken from the cats (GI, GII and GIII), nor their testis and epididymis (PCR, bioassay, histopathological and immunohistochemical analyzes). These results make it possible to infer that sexual transmission in domestic cats is not an important route of infection in the spread of toxoplasmosis among cats